2014
DOI: 10.3945/jn.113.188474
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Education Mitigates the Negative Effects of Higher Income on the Double Burden of Child Stunting and Maternal Overweight in Rural Mexico

Abstract: Globally, the rate at which maternal overweight and obesity increase with rising wealth is higher than the accompanying decline in the prevalence of child stunting, resulting in the double burden of malnutrition. The positive association between household wealth and child linear growth is larger in households with a more educated mother. However, whether a similar positive and synergistic association between maternal education and household wealth is observed for maternal body weight is unknown. Our objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 26 publications
4
56
1
6
Order By: Relevance
“…In addition to the implementation of policies to increase the level of formal education among women, IYCF education programs should be targeted toward women with little formal education, because higher maternal nutrition knowledge has been demonstrated to partially compensate for low education in some contexts (39,49). Although it was not evident from our middle-income study setting, it should be noted that the beneficial influence of maternal knowledge or formal education on child growth is understood to be dependent on a minimum level of access to resources (39,(50)(51)(52)(53). Nonetheless, our findings support the growing interest in increasing maternal educational attainment as a potential intervention toward improving child health outcomes (18,(54)(55)(56).…”
Section: Discussionmentioning
confidence: 91%
“…In addition to the implementation of policies to increase the level of formal education among women, IYCF education programs should be targeted toward women with little formal education, because higher maternal nutrition knowledge has been demonstrated to partially compensate for low education in some contexts (39,49). Although it was not evident from our middle-income study setting, it should be noted that the beneficial influence of maternal knowledge or formal education on child growth is understood to be dependent on a minimum level of access to resources (39,(50)(51)(52)(53). Nonetheless, our findings support the growing interest in increasing maternal educational attainment as a potential intervention toward improving child health outcomes (18,(54)(55)(56).…”
Section: Discussionmentioning
confidence: 91%
“…In Benin, Reed, Habicht, and Niameogo (1996) find that the effect of maternal schooling was insignificant in the lowest stratum, positive and significant in the intermediate socioeconomic stratum, and weakly positive in the best socioeconomic category. In Mexico, Leroy et al (2014) find that maternal schooling mitigates the potentially negative association between increasing wealth and maternal weight, while fostering the positive association between household wealth and child linear growth. Evidence from Bangladesh suggests that the effect of women's empowerment varies with wealth: Sraboni et al (2014), using the WEAI, have shown that the positive effect of different dimensions of women's empowerment on calorie availability and dietary diversity is greater for smaller landowners, that is, for less well-off households.…”
Section: Linkages Between Empowerment Production and Nutritionmentioning
confidence: 83%
“…The literature on maternal education and nutrition suggests that socioeconomic status and maternal education interact (see Leroy, Habicht, Gonzalez De Cossio, & Ruel, 2014 and resources cited therein), although the direction of interaction may vary across socioeconomic status. In Benin, Reed, Habicht, and Niameogo (1996) find that the effect of maternal schooling was insignificant in the lowest stratum, positive and significant in the intermediate socioeconomic stratum, and weakly positive in the best socioeconomic category.…”
Section: Linkages Between Empowerment Production and Nutritionmentioning
confidence: 99%
“…Selain itu, dengan penghasilan yang rendah, ibu tidak mampu untuk melindungi dan menjaga keseimbangan berat badan ketika hamil. 31 Hasil penelitian Djaali dan Eryando, 32 menemukan bahwa anak yang terlahir dengan berat badan yang rendah memiliki ibu dengan tingkat pendidikan yang rendah pula. Berbeda dengan hasil penelitian yang dilakukan oleh Nurcahyani dan Trihandini, 33 anak yang dilahirkan dengan berat lahir yang rendah disebabkan karena ibunya masih belum berkeinginan untuk hamil sebelumnya.…”
Section: Pembahasanunclassified